Giant cell tumor of bone: Epidemiological profile (fifth version) – A study protocol (Research, Society and Development, 2022)
The giant cell tumor of bone (GCTB) represents approximately 5% of primary bone tumors, and more than half of cases affect individuals between 20 and 50 years of age. Despite being a benign neoplasm, 3 to 5% of cases may show pulmonary metastases, besides it has high potential for bone destruction at the main site of the lesion, often in the epiphyses of long bones, which may lead to serious functional problems in affected patients. Multidisciplinary treatment of GCTB has been a cause for discussion in the last decade due to the discovery of drugs such as denosumab that prevent tumor progression and may be useful in cases of patients with local recurrences and unresectable tumors. The therapeutic basis of GCTB remains the isolated surgical treatment by intralesional (with adjuvants), marginal or wide resection. Intralesional treatment presents higher rates of recurrence, however it preserves the adjacent joint function and much of the individual bone stock. Resection with wide margins presents lower recurrence rates but has shown worse functional results and frequent complications in bone reconstructions. Current knowledge of GCTB surgical outcomes has been based on major world series - there is a lack of Brazilian epidemiological and surgical data on this specific type of neoplasm, except for a few series of cases. The primary objective of this paper is to identify the epidemiological profile of GCTB; the secondary objectives are to describe the surgical aspects in the main diagnostic centers and treatment of bone tumors, to analyze the clinical and surgical aspects of patients with GCTB of wrist and hand, and to analyze the clinical and surgical aspects of patients with knee GCTB. These findings may help in the maintenance or change of national guidelines for the treatment of GCTB. This study protocol was submitted to ethical assessment under the CAAE (Ethical Appreciation Presentation Certificate) registry No. 94280918.0.0000.5327 (5th version), evaluated through the substantiated opinion No. 4.770.705, and approved by the Institutional Research Ethics Committee on June 12, 2022.